Development of Method for Safety Factor on Automobile Roads - Yu. A. Bogdanovich (Наука и техника)
In order to develop method concerning safety factors on automobile roads the paper proposes to account climatic factors that exert additional influence on the character of vehicle’s movement. Jt is recommended to take into account not only difference in speed but the state of a roadway as well. Such method makes it possible to be more objective in evaluation of danger rate of roadway sections that is rather important for proper selection of plan and longitudinal profile of automobile roads.